2008
DOI: 10.1111/j.1553-2712.2007.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Subinternship: Does a Standard Clinical Experience Improve Performance Outcomes?

Abstract: Background: The emergency medicine (EM) subinternship provides a varied experience for senior medical students depending on gender, specialty choice, and interest. A didactic curriculum can be standardized, but the clinical component is difficult to control. Students can be directed to see patients with specific chief complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 6 publications
1
20
0
2
Order By: Relevance
“…Our results are in line with the work of Debehnke who showed that readings augmented with case conferences improved student knowledge (18). Lampe et al showed improved outcomes when clinical requirements were added to standard didactics (13). In the current study, we found that combining clinical learning with instructor-moderated case-based conferences improved learning outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with the work of Debehnke who showed that readings augmented with case conferences improved student knowledge (18). Lampe et al showed improved outcomes when clinical requirements were added to standard didactics (13). In the current study, we found that combining clinical learning with instructor-moderated case-based conferences improved learning outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…These evidence-based approaches have been varied and have included assessing whether education modalities such as simulation, personal digital assistant (PDA) logs, and chief-compliant based requirements are effective educational advances (6,11,12). A study by Lampe et al showed improved scores on general EM examinations at the end of the clerkship when students were required to see patients with particular chief complaints (13). Approximately 44% of medical school respondents in a recent national survey now require students to see a list of specific patient chief complaints (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, a virtual program lacks the ability to obtain first-hand experience and exposure in the ED. An EM rotation has been shown to provide a unique educational opportunity, and efforts have been made to create a uniform EM course (15)(16)(17)(18)(19). However, a required third-year EM rotation was found to have no correlation with the number of students applying or matching in EM (20).…”
Section: Discussionmentioning
confidence: 99%
“…Data analyses were appropriate in all but one study (Martin et al 2000), and all were beyond the descriptive level. Four studies reported outcome only at student reaction (Kirkpatrick level 1) (Dolmans et al 2002;O'Hara et al 2002;Saywell et al 2002;van der Zwet et al 2010), whereas 10 studies measured knowledge and/or skills (Kirkpatrick 2) (Gruppen et al 1993;Schwiebert et al 1993;McLeod et al 1997;Jacobson et al 1998;Greenberg & Getson 1999;Boots et al 2008;Lampe et al 2008;Nomura et al 2008;Duke et al 2011;Yu et al 2011). Less than half of the studies (n ¼ 8) measured outcomes up to the behavioural level (Kirkpatrick 3) (Chatenay et al 1996;Jolly et al 1996;McManus et al 1998;Ahmed & Hughes 1999;Martin et al 2000;Sorensen et al 2004;Wimmers et al 2006a;Fung et al 2007).…”
Section: Methodological Quality Of Studiesmentioning
confidence: 99%
“…In three of these studies, similar sites were compared (Chatenay et al 1996;Wimmers et al 2006a;Yu et al 2011), three others compared academic vs. nonacademic sites (Schwiebert et al 1993;McLeod et al 1997;Nomura et al 2008) and two compared inpatients and outpatients (Jacobson et al 1998;Duke et al 2011). Four studies evaluated the learning effects of an intervention: the introduction of a rotation (Gruppen et al 1993), a skill-training programme (Boots et al 2008), identification of 10 preselected complaints (Lampe et al 2008) and a new internship (Nomura et al 2008). Two studies compared groups of medical students at a different phase of their training (Ahmed & Hughes 1999;Boots et al 2008).…”
Section: Types Of Studiesmentioning
confidence: 99%